Research progress on sources and production methods of natural fibrinolytic enzymes - PENG Cuiying, WANG Panpan, DENG Xiongwei, XIE Xiaomei, WENG Meizhi (Zhongguo niangzao)
Cardiovascular diseases (CVDs) took the lives of 17.9 million people each year, which accounted for 31% of all global deaths. Among all kinds of cardiovascular diseases, thrombosis is the most common one. How to prevent and treat thrombosis effectively is a major global medical problem. In the prevention and treatment of thrombosis, fibrinolytic enzyme has great potential. Fibrinolytic enzyme is proteolytic enzyme and is important in the prevention and treatment of thromboembolic diseases. In this paper, the mechanism of thrombosis formation and fibrinolytic enzymes was reviewed, the sources of fibrinolytic enzymes (marine microorganisms, fermented food microorganisms, plants and animals) and production methods were summarized, and the production methods of fibrinolytic enzymes were summarized and prospected, in order to provide reference for the research in related fields.